2023
DOI: 10.1101/2023.08.28.555225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein Coronas on Functionalized Nanoparticles Enable Quantitative and Precise Large-Scale Deep Plasma Proteomics

Ting Huang,
Jian Wang,
Alexey Stukalov
et al.

Abstract: BackgroundThe wide dynamic range of circulating proteins coupled with the diversity of proteoforms present in plasma has historically impeded comprehensive and quantitative characterization of the plasma proteome at scale. Automated nanoparticle (NP) protein corona-based proteomics workflows can efficiently compress the dynamic range of protein abundances into a mass spectrometry (MS)-accessible detection range. This enhances the depth and scalability of quantitative MS-based methods, which can elucidate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…We demonstrated that timsTOF HT identified up to 76% more plasma peptide precursors and resulted in a >2-fold increase in reproducible precursors (CV < 20%) compared to timsTOF Pro 2. In all experiments, the use of the Proteograph improved the performance of the mass spectrometry platform consistent with the significant improvement in depth of coverage described in prior publications that have ranged from 5 − 8X. Proteograph plasma analyzed at 600–1200 ng peptide loading mass on an EvosepOne-timsTOF HT enabled deep plasma proteome profiling with exceptional quantitative reproducibility and linearity. Qualitative and quantitative improvements of timsTOF HT translated into an approximate 50% increase in total and statistically significant ( q < 0.05) plasma precursors between lung cancer and control cohorts when plasma processed by the Proteograph were analyzed by timsTOF HT compared to Pro 2.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We demonstrated that timsTOF HT identified up to 76% more plasma peptide precursors and resulted in a >2-fold increase in reproducible precursors (CV < 20%) compared to timsTOF Pro 2. In all experiments, the use of the Proteograph improved the performance of the mass spectrometry platform consistent with the significant improvement in depth of coverage described in prior publications that have ranged from 5 − 8X. Proteograph plasma analyzed at 600–1200 ng peptide loading mass on an EvosepOne-timsTOF HT enabled deep plasma proteome profiling with exceptional quantitative reproducibility and linearity. Qualitative and quantitative improvements of timsTOF HT translated into an approximate 50% increase in total and statistically significant ( q < 0.05) plasma precursors between lung cancer and control cohorts when plasma processed by the Proteograph were analyzed by timsTOF HT compared to Pro 2.…”
Section: Discussionsupporting
confidence: 66%
“…Our data offer a comprehensive comparison of the timsTOF HT and Pro 2 systems for neat and Proteograph plasma proteomic profiling across a wide range of plasma peptide loading masses (100–1200 ng) and liquid chromatography (LC) gradients [100 samples per day (SPD), 60 SPD, 30 SPD]. The Proteograph workflow with the Proteograph Assay Kit (v1.2) leverages 5 distinct nanoparticles (NP1–5), in an automated workflow reproducibly compressing the dynamic range of the plasma proteome and thus enabling deeper proteome profiling. In this paper, we propose an optimal range of liquid chromatography–mass spectrometry (LC–MS) conditions for deep and reproducible plasma proteomics analysis. Our data showcase the potential of timsTOF HT together with the Proteograph to identify putative cancer biomarkers in plasma using cohorts designed to exhibit distinct proteomic profiles [i.e., samples from 20 patients with stage IV nonsmall cell lung cancer (NSCLC) and 20 noncancer controls].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were then eluted by positive pressure and dried down before digestion. Alternatively, samples were depleted by perchloric acid precipitation according to the protocol in Viode et al 12 Healthy pooled plasma samples were also prepared by treatment with proprietary nanoparticle from Seer Proteograph TM , as described in Ferdosi et al 8,13 This automated platform offers a complete workflow from enrichment of low abundant proteins to peptide solution ready to be analyzed by LC-MS/MS using proprietary reagents. 5 µL of naïve plasma or dried depleted plasma samples were digested on the i7 automation workstation (Beckman Coulter).…”
Section: Methodsmentioning
confidence: 99%
“…Providing both high sensitivity, scan speed up to 200 Hz, and highly parallelizable acquisition, various groups have described impressive gains in protein identifications and throughput with good reproducibility. [1][2][3][4][5][6][7][8][9][10][11] Users have reported remarkable levels of depth achievable through this new instrumentation in cellular, plasma and metaproteomic studies. In the context of clinical proteomics, large scale analysis of patient cohorts must combine precision, reproducibility, and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…Our study leverages a novel nanoparticle-based untargeted LC-MS/MS workflow, which has shown exceptional capacity for in-depth plasma protein coverage, quantitative performance, and analysis throughput 8,[13][14][15][16] . Here, we applied this workflow to assess the proteomic changes in a cohort of 12 volunteers following two doses of the Pfizer-BioNTech mRNA COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%